Aplikasi Isolat Bakteri Hidrokarbonoklastik asal Rizosfer Mangrove pada Tanah Tercemar Minyak Bumi - Nuni Gofar (Research Center for Sub-optimal Lands (PUR-PLSO), Universitas Sriwijaya, 2012)
Gofar. 2012. Application of Hydrocarbonoclastic Bacteria Isolates from Mangrove Rhizosphere on Petroleum Polluted Soil. JLSO 1(2):123-129.This research was aimed at studying the ability of hydrocarbonoclastic bacteria to reduce total petroleum hydrocarbon of petroleum polluted soil. The hydrocarbonoclastic bacteria were isolated from rhizosphere of mangrove grown on petroleum contaminated soil in Sungsang, Sumatra Selatan. The samples were taken using a defined sampling method from the oil contaminated areas. Soil samples around the roots of mangrove plants were randomly taken in the contaminated area. Isolates obtained from the isolation and selection of bacteria from mangrove forests were overhauled at the laboratory-scale using oil-enriched medium following a completely randomized design. Nine isolates of hydrocarbonoclastic bacteria were found to be capable of growing on petroleum contained medium in vitro. Two best isolates in degrading petroleum hydrocarbon compound were Pseudomonas alcaligenes (I5) and Alcaligenes facealis (I8). P. alcaligenes and A. facealis were able to decrease TPH up to 63% and 70% respectively. The ability of these isolates in degrading hydrocarbon compound was 6.5-7.0 times higher than the control.